Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Sport Stasion Di Mall Solo Paragon - Putra, Novarizal Pratama; , Ihwan Susila, M. Si., PhD (2017)
This study aimed to determine the effect of service quality on customer satisfaction. The sample in this study were employees who work at Sport Station In Solo Paragon Mall totaling 124 respondents. The sampling technique in this research is convenience sampling. Data analysis methods used were normality test, multicollinearity, heteroskedasitas test and test multiple linear regression analysis with t-test, F, and the coefficient of determination (R2). In this study the data meet for a normal distribution. Hypothesis tests showed that the Reliability and Responsiveness have significan, while the variable empathy, tangibility, Assurance does not have a significant effect on consumer satisfaction. At f test showed that together Empathy, Reliability, Responsiveness, tangibility, and Assurance significant effect on customer satisfaction. The coefficient of determination (R2) of 0.399%.